Peminatan Olahraga Paralayang pada Siswa SMP - Adha, Intan Syafira; Wibowo, Sapto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to see a picture of the potential for developing paragliding sports in Indonesia, especially involving geographical areas rich in mountains and hills. Even though this sport was included in the 2000 PON XV program in East Java, students' interest in paragliding seems to be outside the development of this sport. Although various paragliding events in Indonesia stimulate student interest, the decline in the number of athletes at the secondary education level shows challenges. This research uses descriptive methods and a quantitative approach to assess the level of interest of Ciputra Surabaya Middle School students in paragliding. Using a sampling method involving quota techniques and random analysis, this research focuses on quantitative data with the aim of testing predetermined hypotheses. The research results showed that the average interest of students in class 8 was 62.74, while in class 9, it was 63.32. The frequency results show that student interest is in the medium to high category, with most students falling into that category. The conclusion is that Ciputra Surabaya Middle School students are interested in paragliding. Keywords: Sports, Paragliding Championship, Middle School